DTM-FDM hybrid approach to unsteady MHD Couette flow and heat transfer of dusty fluid with variable properties. (June 2017) - Mosayebidorcheh, Sobhan; Makinde, O.D.; Ganji, D.D.; Abedian Chermahini, M.
Abstract: The present paper studies the unsteady MHD Couette flow and heat transfer of dusty fluid between two parallel plates and the effects of the temperature dependent properties on it. The viscosity and thermal conductivity are considered as exponential and linear functions of the temperature, respectively. An external uniform magnetic field and a constant pressure gradient are considered in directions of the main flow and perpendicular of the plates, respectively. A hybrid technique based on differential transform method (DTM) and finite difference method (FDM) is used to solve the governing coupled flow and heat transfer equations. The effects of the magnetic field (Hartman number) and temperature dependent of the thermal conductivity and viscosity are discussed by considering the velocity and temperature profiles of the clean fluid and dust particle. Applying a magnetic field in the present problem decreases the value of the Nusselt number and skin friction coefficient.